2011
DOI: 10.1002/jwmg.135
|View full text |Cite
|
Sign up to set email alerts
|

Location and agricultural practices influence spring use of harvested cornfields by cranes and geese in Nebraska

Abstract: Millions of ducks, geese, and sandhill cranes (Grus canadensis; hereafter cranes) stop in the Central Platte River Valley (CPRV) of Nebraska to store nutrients for migration and reproduction by consuming corn remaining in fields after harvest. We examined factors that influence use of cornfields by cranes and geese (all mid‐continent species combined; e.g., Anser, Chen, and Branta spp.) because it is a key step to efficient conservation planning aimed at ensuring that adequate food resources are available to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 23 publications
4
34
0
Order By: Relevance
“…Baldassarre et al (1983) proposed that burning stubble may make corn more available to birds because it removes litter that covers residual corn, although this was not a commonly used management practice in the CPRV during our study. Despite lower corn abundance, Anteau et al (2011) noted that sandhill cranes in the CPRV used mulched cornfields more than any other treatment, potentially because cranes favored fields with less standing stubble or because mulched fields may have higher densities of other food items (e.g., invertebrates). Thus, field use by cranes may be influenced by trade‐offs among desirable structure (e.g., low cover), abundance of residual corn, and efficiency of foraging through litter.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Baldassarre et al (1983) proposed that burning stubble may make corn more available to birds because it removes litter that covers residual corn, although this was not a commonly used management practice in the CPRV during our study. Despite lower corn abundance, Anteau et al (2011) noted that sandhill cranes in the CPRV used mulched cornfields more than any other treatment, potentially because cranes favored fields with less standing stubble or because mulched fields may have higher densities of other food items (e.g., invertebrates). Thus, field use by cranes may be influenced by trade‐offs among desirable structure (e.g., low cover), abundance of residual corn, and efficiency of foraging through litter.…”
Section: Discussionmentioning
confidence: 99%
“…Tilled fields had the lowest corn density of any treatment, likely because corn cobs and kernels were broken up and buried during tillage. Despite low corn abundance, Anteau et al (2011) noted that geese in the CPRV used tilled fields more than other treatments. Jorde et al (1983) suggested that foraging efficiency of mallards ( Anas platyrhynchos ) was higher in tilled fields because of a decrease in litter at the surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Snow geese (Chen caerulescens) select waste corn over wheat and soybeans (Frederick and Klaas, 1982). Canada goose (Branta canadensis) and other waterfowl have demonstrated differential field use based on waste corn density (Anteau et al, 2011). As cover, fields with standing stubble of cereal crops and oilseed were used by more granivores than fields with traditional tillage in Europe and North America (Castrale, 1985;Donald and Forrest, 1995;Chamberlain et al, 1999;Gillings et al, 2005;Kopij, 2008;Kragten and de Snoo, 2008).…”
Section: Introductionmentioning
confidence: 99%